Pembelajaran melalui strategi REACT untuk meningkatkan kemampuan pemahaman matematis siswa sekolah menengah kejuruan - Linda Herawati (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This research is aimed at improving the ability of students’ mathematical understanding through REACT strategy. This research method is a quasi-experimental study with the non randomized study design pretest-posttest control group design. Samples were students of class X of one vocational school in Tasikmalaya. The instruments used were pretest and posttest ability of students’ mathematical understanding. The data were analyzed quantitatively. The results showed that: (1) students who obtain learning through REACT strategy had significantly better improvement than students who received conventional learning (2) Students who earn learning with REACT strategy shows there is a difference compared with students who received conventional learning to be reviewed on the level of high, medium, and low (3) students who earn learning with REACT strategy by category ability of students to the ability of students’ mathematical understanding is better than conventional learning. This means REACT strategy can improve comprehension.